Depositional age and correlation of the Oonah Formation: refining the timing of Neoproterozoic basin formation in Tasmania. Issue 3 (3rd April 2018) - Mulder, J. A.; Berry, R. F.; Halpin, J. A.; Meffre, S.; Everard, J. L.
ABSTRACT: The Proterozoic Oonah Formation comprises a thick sequence of turbidites and mafic rocks that is widely exposed in western and northern Tasmania. The regional significance of the Oonah Formation is poorly understood as its contacts are faulted and estimates of its depositional age range from 1450 Ma to 700 Ma. Here we refine the depositional age of the Oonah Formation and clarify its relationship to other Proterozoic sequences in Tasmania. Magmatic apatite from the syn-sedimentary Cooee Dolerite has a 207 Pb-corrected 238 U/ 206 Pb age of 733 ± 9 Ma that provides a robust estimate of the depositional age of the Oonah Formation. The Oonah Formation contains abundant 750 Ma detrital monazite and has detrital zircon age populations at 1800–1700 Ma, 1590 Ma, and 1450 Ma. The new age and provenance data support the interpretation that the Oonah Formation is a lateral equivalent of the base of the Togari Group and correlatives in Tasmania. We demonstrate that the stratigraphy and provenance of Neoproterozoic strata in Tasmania differ from time-equivalent sequences in Adelaide Rift Complex but are similar to the Pahrump Group (Death Valley, California) and the Cobham Formation (Transantarctic Mountains), which supports a southwest Laurentia—Tasmania—East Antarctica connection within supercontinent Rodinia.